GROWING INTEREST IN ENTREPRENEURSHIP BY UTILIZING LOCAL RESOURCE - Lucky Radi Rinandiyana; Tine Badriatin; Linda Septiana; Elis Listiana Mulyani (Pasundan International of Community Services Journal (PICS-J), 2020)
Siliwangi University as an educational institution that has one of the responsibilities of community service, Siliwangi University conducts Thematic Work Lecture (KKN) activities in the context of community empowerment through the introduction of the concept of entrepreneurship in several areas of Tasikmalaya Regency, one of them in Dirgahayu Village, Kadipaten District is a village which is located in a mountainous area which has 6 hamlets namely Trowek, Palumbungan, Cijotang, Cipeusing, Cilongkeang and Gekbrong. The focus that we take in Dirgahayu Village is to foster community interest in entrepreneurship, in Dirgahayu village itself there are already a few people who have started entrepreneurship, it's just that the community is still lacking in innovation or utilization of local resources in the village. This is due to the lack of good technology utilization. This service uses counseling method which was attended by 30 people of Dirgahayu Village, especially Youth Organization and PKK ladies. Aiming to provide knowledge and understanding of entrepreneurship by utilizing local resources. The results of this activity are processed cassava products in the form of chips with seblak flavored innovation, however there is still a need to improve product design for product packaging to make it more attractive.